Microalgal-based biochar in wastewater remediation: its synthesis, characterization and applications - Law, Xin Ni; Cheah, Wai Yan; Chew, Kit Wayne; Ibrahim, Mohamad Faizal; Park, Young Kwon; Ho, Shih Hsin; Show, Pau Loke (Academic Press, 2022)
Microalgae are drawing attentions among researchers for their biorefinery use or value-added products. The high production rate of biomasses produced are attractive for conversion into volatile biochar. Torrefaction, pyrolysis and hydrothermal carbonization are the recommended thermochemical conversion techniques that could produce microalgal-based biochar with desirable physiochemical properties such as high surface area and pore volume, abundant surface functional groups, as well as functionality such as high adsorption capacity. The characterizations of the biochar significantly influence the mechanisms in adsorption of pollutants from wastewaters. Specific adsorption of the organic and inorganic pollutants from the effluent are reviewed to examine the adsorption capacity and efficiency of biochar derived from different microalgae species. Last but not least, future remarks over the challenges and improvements are discussed accordingly. Overall, this review would discuss the synthesis, characterization and application of the microalgal-based biochar in wastewater.